The Influence of Window Dressing and Leverage on Investment Decisions in Consumer Non-Cyclical Companies Listed on the Indonesia Stock Exchange - Riyan Ardika; Ilham Wahyudi; Muhammad Ridwan (International Forum of Researchers and Lecturers, 2025)
Consumer non-cyclical companies represent a stable sector that provides essential goods and services, often attracting investors seeking long-term, low-volatility opportunities. This study investigates how financial strategies—specifically window dressing and leverage—influence investment decisions in 68 consumer non-cyclical companies listed on the Indonesia Stock Exchange for the period 2019–2023. Investment decisions are measured using two key valuation indicators: Price to Book Value (PBV) and Price to Earnings Ratio (PER). Window dressing is quantified through changes in quarterly cash holdings, while leverage is proxied by the Debt to Equity Ratio (DER). Employing a quantitative descriptive method, this research uses purposive sampling and multiple linear regression analysis, preceded by classical assumption tests. The findings reveal that both window dressing and leverage have a significant positive effect on PBV, indicating that these factors play a role in shaping market perceptions of firm value. Conversely, neither variable has a significant influence on PER, suggesting that investors in this sector rely more on consistent fundamentals than on short-term financial appearances or capital structure when evaluating profitability. These results support signaling theory, emphasizing that while financial signals can influence market behavior, their effectiveness depends on the credibility of the signal and the investor’s focus. This study provides practical implications for managers aiming to enhance firm value and for investors seeking to interpret financial signals more accurately.